Energetics, Biomechanics, and Performance in Masters' Swimmers: A Systematic Review - Ferreira, Maria I (2020)
This study aimed to summarize evidence on masters' swimmers energetics, biomechanics, and performance gathered in selected studies. An expanded search was conducted on 6 databases, conference proceedings, and department files. Fifteen studies were selected for further analysis. A qualitative evaluation of the studies based on the Quality Index (QI) was performed by 2 independent reviewers. The studies were thereafter classified into 3 domains according to the reported data: performance (10 studies), energetics (4 studies), and biomechanics (6 studies). The selected 15 articles included in this review presented low QI scores (mean score, 10.47 points). The biomechanics domain obtained higher QI (11.5 points), followed by energetics and performance (10.6 and 9.9 points, respectively). Stroke frequency (SF) and stroke length (SL) were both influenced by aging, although SF is more affected than SL. Propelling efficiency (ηp) decreased with age. Swimming performance declined with age. The performance declines with age having male swimmers deliver better performances than female counterparts, although this difference tends to be narrow in long-distance events. One single longitudinal study is found in the literature reporting the changes in performance over time. The remaining studies are cross-sectional designs focusing on the energetics and biomechanics. Overall, biomechanics parameters, such as SF, SL, and ηp, tend to decrease with age. This review shows the lack of a solid body of knowledge (reflected in the amount and quality of the articles published) on the changes in biomechanics, energetics, and performance of master swimmers over time. The training programs for this age-group should aim to preserve the energetics as much as possible and, concurrently, improve the technique. Training sessions should feature a higher percentage of technical drills with the goal of enhancing the swim technique. Another goal should be the association of technique enhancement with aerobic and anaerobic sets, enabling the swimmer to improve the swimming efficiency.